Gestational weight gain charts for Latin American adolescents (2023)
ABSTRACT: Monitoring gestational weight gain (GWG) throughout pregnancy among adolescents is important for detecting individuals at risk and timely intervention. However, there are no specific tools or guidelines for GWG monitoring of this group. We aimed to construct GWG charts for pregnant adolescents (10–19 years old) according to pre-pregnancy body mass index (BMI) using a pooled dataset from nine Latin American countries. Datasets from Argentina, Brazil, Chile, Colombia, Mexico, Panama, Paraguay, Peru, and Uruguay collected between 2003 and 2021 were combined after data cleaning and harmonization. Adolescents free of diseases that could affect GWG and who gave birth to newborns weighing between 2,500–4,000 g and free of congenital malformations were included. Multiple imputation techniques were applied to increase the sample size available for underweight and obesity categories. Generalized Additive Models for Location, Scale, and Shape were used to construct the charts of GWG according to gestational age. Internal and external validation procedures were performed to ensure that models were not over-adjusted to the data. The cohort included 6,414 individuals and 29,414 measurements to construct the charts and 1,684 individuals and 8,879 measurements for external validation. The medians (and interquartile ranges) for GWG at 40 weeks according to pre-pregnancy BMI were: underweight, 14.9 (11.9–18.6); normal weight, 14.0 (10.6–17.7); overweight, 11.6 (7.7–15.6); obesity, 10.6 kg (6.7–14.3). Internal and external validation showed that the percentages above/below selected percentiles were close to those expected, except for underweight adolescents. These charts describe the GWG throughout pregnancy among Latin American adolescents and represent a significant contribution to the prenatal care of this group. GWG cut-offs based on values associated with lower risks of unfavorable outcomes for the mother-child binomial should be determined before implementing the charts in clinical practice.